The Role of Website-Based Learning Media in Enhancing Students' Conceptual Understanding: A Literature Review - Ahmad Hardyan Isnaini; Irman Muliadi; Lalu Azikri Amrullah; Holis Angga Saputra (Indonesian Journal of Teacher Education, 2026)
The development of information and communication technology has encouraged the use of website-based learning media as an innovation in the educational process. This study aims to analyze the role of website-based learning media in improving students’ conceptual understanding through a literature review approach. The method used is a literature review by examining scientific articles published between 2015 and 2024. The systematic selection process followed standard protocols, including identification of 50 relevant records, screening based on inclusion criteria (educational level and conceptual understanding variables), and eligibility assessment. Based on this process, 15 articles were selected and analyzed qualitatively. The results show that website-based learning media can enhance students’ conceptual understanding through the visualization of abstract materials, interactive content delivery, and support for self-directed and contextual learning. In addition, this media also increases students’ motivation and engagement in the learning process. However, its implementation still faces challenges such as limited infrastructure and the readiness of human resources. Therefore, the development and utilization of website-based learning media need to be optimized to support more effective learning in the digital era.